Effects of Exogenous Interleukin-6 during Pseudomonas aeruginosa Corneal Infection - Cole, Nerida (American Society for Microbiology, 2001)
Lack of interleukin-6 (IL-6) during Pseudomonas aeruginosa corneal infection leads to more severe disease with changes in neutrophil recruitment. Exogenous IL-6 leads to increased efficiency of neutrophil recruitment and reduced bacterial loads in corneal infection in both IL-6 gene knockout and wild-type mice. This may be mediated by IL-6 increasing the production of corneal macrophage inflammatory protein 2 and intercellular cell adhesion molecule 1. We conclude that effective recruitment of neutrophils into the cornea is dependent on the production of IL-6 and that early augmentation of IL-6 may be protective in corneal infection.